REDUCING COSTS BY INTEGRATING THE THEORY OF CONSTRAINTS AND THE JUST-IN-TIME PRODUCTION SYSTEM - pcadmin, Hoda Mohamed Khader (Scholar Express Journals, 2024)
The JIT system is described as a philosophy that combines modern and old technologies. It is a production and inventory management system that aims to produce and deliver goods exactly at the moment they are needed in the production process or by the customer, making its application possible in all areas of business from production, purchasing and delivery. The JIT philosophy is to operate a simplified and efficient production system, capable of optimal use of resources, in preparation for meeting the real demands of consumers with the required quality and quantity, on time and at an appropriate price. The goal of JIT is to remove all activities that burden the facility with indirect costs and unnecessary expenses, and to eliminate waste, including excess inventory, excess production and waiting times, and to avoid production obstacles, through integration between the main aspects of the subsystems and highlighting them in a homogeneous formation, and an interactive system through integration with the theory of constraints to remove all obstacles. This can lead to significant cost savings and increased efficiency, as it requires a high level of accuracy and responsiveness to changes in demand and production requirements.
Keywords: Theory of Constraints; Just-in-time production system; Cost reduction